No-till technology as a promising method to improve productivity of winter wheat - S. A. Pavlov; A. S. Popov (Зерновое хозяйство России, 2018)
The article presents a description of the main technologies of winter wheat cultivation. The conventional tillage in comparison with a no-till technology has been considered. The article gives the study results obtained by various researchers in cultivation technology of winter wheat. The authors consider both advantages and disadvantages of the conventional and no-till technologies. The main effects of the various cultivation methods on the state of soil root layer have been studied. The article presents a separate study of the aspects connected with the influence of the conventional and no-till technologies upon agrophysical properties of soil. The work considers the main reasons of erosion on the fertile soil layers and the effect of tillage on prevention of these processes. The authors present the data about the effect of various tillage methods on the infection of winter wheat by pests and on weeds distribution.